Tingkat Prokrastinasi Akademik Siswa Kelas XI SMK Negeri 7 Semarang - Hanifa, Itsna Putri Nur; Rakhmawati, Dini; Gunawan, Singgih (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This research aims to determine the level of academic procrastination that occurs at SMK Negeri 7 Semarang among class XI students. The research method used is descriptive quantitative. The research population is all class XI of SMK N 7 Semarang, totaling 699 students. From this population, 102 students will be taken using probability sampling techniques. The measuring instrument used is a Likert scale using four aspects consisting of 28 statement items. The instrument uses adaptive by Faozi (2022). Data analysis uses the descriptive percentage method. It can be concluded from this research that academic procrastination at SMK N 7 Semarang is predominantly in the medium category with a percentage of 63%. Apart from that, there are 33% of students in the low category and 4% of students in the high category.